When and How Workplace Helping Promotes Deviance? An Actor-Centric Perspective - Zhang, Hao; Lin, Chunpei; Lai, Xiumei; Liu, Xiayi (Frontiers in Psychology, 2022)
Despite the vast academic interest in workplace helping, little is known about the impact of different types of helping behaviors on physiological and behavioral ramifications of helpers. By taking the actor-centric perspective, this study attempts to investigate the differential impacts of three kinds of helping behaviors (caring, coaching and substituting helping) on helpers themselves from the theory of resource conservation. To test our model, 512 Chinese employees were surveyed utilizing a three-wave time-lagged design, and we found that caring and coaching helping were negatively associated with workplace deviance whereas substituting helping was positively associated with subsequent workplace deviance. Emotional exhaustion mediated the effects of three helping behaviors on subsequent workplace deviance. Moreover, employees’ extrinsic career goals influenced the strength of the relationship between three helping behaviors and emotional exhaustion and the indirect effects of three helping behaviors on subsequent workplace deviance via emotional exhaustion. We discuss the implications of our findings for both theories and practices.